Health and the Origins of the Miqveh - Gordon, Benjamin D. 1977- (2020)
Abstract Use of rock-cut stepped pools for immersion in harvested rainwater is first attested in Judean source material of the second century BCE and on archaeological record shortly thereafter. As argued here, the practice became widespread due to the impact of Greco-Roman ideas about health and well-being. Immersion of the body in water was seen in the Greek medical tradition as a beneficial activity; it balanced the humors, opened harmful blockages in the skin membrane, and helped facilitate unction. Once these ideas became widespread in Judea, local purification rituals followed, and began incorporating immersion in water. The rabbinic dichotomy between purification and cleansing was likely irrelevant for most Judeans in the late Second Temple period, who probably also saw immersion as beneficial for personal hygiene. For this reason, stepped pools nearly disappear from archaeological record with the rise of public bathhouses, which offered the convenience of large and well-maintained immersion pools in exchange for a fee.
Keywords: Medicine; Health; Judea; Purity; Miqveh; bathing